2020
DOI: 10.1002/iid3.318
|View full text |Cite
|
Sign up to set email alerts
|

β‐Lactam allergy testing and delabeling—Experiences and lessons from Singapore

Abstract: Background: β-Lactam allergy is over-reported and this leads to greater healthcare costs. Allergy testing has inherent risks, yet patients who test negative may continue avoiding β-lactams. Objective: To evaluate the safety and diagnostic value of β-lactams allergy testing locally and usage of antibiotics following negative testing. Methods: We performed a retrospective medical record review and follow-up survey of patients who underwent β-lactam testing between 2010 and 2016 at the National Skin Centre, Singa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Most of the labelled patients did not attend the medical appointment to take the challenge and some of them continued to receive non-BL antibiotics in infectious processes after being delabelled. As in other studies, some patients refused to take this type of antibiotics for fear of an allergic reaction 19. This fear, the lack of awareness of the importance of being delabelled or even the panic associated with going to the hospital in a pandemic context were the main reasons why many patients (n=65, 36.9%) did not attend the appointment with the allergist.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Most of the labelled patients did not attend the medical appointment to take the challenge and some of them continued to receive non-BL antibiotics in infectious processes after being delabelled. As in other studies, some patients refused to take this type of antibiotics for fear of an allergic reaction 19. This fear, the lack of awareness of the importance of being delabelled or even the panic associated with going to the hospital in a pandemic context were the main reasons why many patients (n=65, 36.9%) did not attend the appointment with the allergist.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, collection of the history of antibiotic allergy may be a quality tool to safely increase the proportion of patients receiving BL antimicrobials 18. Traditionally, when a patient was labelled as penicillin-allergic all BL antibiotics were avoided, but a recent meta-analysis showed that the risk of cross-reactivity to carbapenems in penicillin-allergic patients is less than 1% 19. Carbapenems were used in 14 (8.0%) of the patients despite them being labelled as ‘BL-allergic’, and none of them had an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…7 Many examples of risk stratification and algorithms have been published recently. 7,[33][34][35][36][37][38][39][40][41][42] Whilst focus remains on patient safety, individual risk stratification means, that in patients considered to be at low risk of allergy a diagnosis can be achieved with fewer resources.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…The approach to allergy to beta‐lactam antibiotics has evolved compared to the more restrictive approach recommended previously 7 . Many examples of risk stratification and algorithms have been published recently 7,33–42 . Whilst focus remains on patient safety, individual risk stratification means, that in patients considered to be at low risk of allergy a diagnosis can be achieved with fewer resources.…”
Section: Drug Provocation Testing With Specific Drug Groupsmentioning
confidence: 99%